PERAN ORANG TUA TERHADAP PEDIDIKAN KARAKTER ISLAMI ANAK DI MASA PANDEMI COVID-19 - Winni Trie Saleha; Rabiyannur Lubis (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
The parents have an important role in children's Islamic character education during the Covid-19 pandemic. Reality states that distance learning with technological sophistication cannot touch the core of education, namely character education. The intensity of many children at home is expected to be used by parents in efforts to educate Islamic characters. So this study aims to describe the role of parents in children's Islamic character education during the covid-19 pandemic at the Parenting School of Nurul Fajri and to find out the supporting and inhibiting factors for the role of parents in children's Islamic character education during the covid-19 pandemic. This study uses qualitative research with naturalistic methods. The data were collected through interviews, observation, and documentation. The informants in this study consisted of the head and five parents who were the administrators and coordinators of the Parenting School Nurul Fajri Cikarang Barat class and five students of SDIT Nurul Fajri. Then, checking the validity of the data using triangulation techniques. The triangulation technique was carried out using the triangulation method and it's re-checking the information from interviews with documentation and observation. The results of this study show that the role of parents is as educators of children's Islamic character, especially honest attitudes, as supervisors and companions for children studying at home to develop the Islamic nature of responsibility, and as motivators who can motivate children to look hard and foster a sincere attitude in worship. And as an example for their children to form an Islamic character of patience, honesty, responsibility, and sincerity. The supporting factors are closeness and good communication between parents and children, the school environment, the environment where they live, religious knowledge, and good collaboration and cooperation between mothers and fathers at home. Then, the most important inhibiting factor is gadgets/mobile phones. Furthermore, during this pandemic, Nurul Fajri's Parenting School seeks to educate parents in strengthening character education through parenting webinars.